PERAN OPERATOR SEKOLAH DALAM MENINGKATKAN MUTU SISTEM INFORMASI MANAJEMEN PENDIDIKAN DI SMPN 3 SAWANG ACEH SELATAN - Marlisa; Safriadi (FITRAH: International Islamic Education Journal, 2023)
This research was conducted to determine the role of school operators in improving the quality of the education management information system at Junior High School 3 Sawang. The research method used is qualitative using a descriptive approach to collect data. The data collection techniques used were observation and interviews. This research was conducted at Junior High School 3 Sawang School by using one school operator as the research object. The results of the research show that school operators play a role and are fully responsible for managing the management information system which has a very, very important influence in achieving improvements in the quality of the education management information system at Junior High School 3 Sawang schools. Data management carried out by school operators is running well, such as school data, teacher data, principal data, and student data. School operators have demonstrated excellent ability and competence in assisting in managing management information systems.